Question #98f3d

2 Answers
Nov 30, 2017

Eeeezy peeeezy....

Explanation:

cos^2theta/(1-sin theta) - 1 =

(1-sin^2theta)/(1-sin theta) - (1-sintheta)/(1-sintheta)

= (-sin^2theta + sintheta)/(1-sintheta)

= (sintheta(1-sintheta))/(1-sintheta)

= sintheta

GOOD LUCK

Nov 30, 2017

See below.

Explanation:

Not sure if you are asking to prove this, or you are looking to solve it as an equation for specific values of theta.

This is not an identity, so it can't be proved.

LHS

Let theta=pi/2

(cos^2(pi/2))/(1-sin(pi/2))-1=0/(1-1)-1=( division by zero)

RHS:

sin(pi/2)=1

LHS!=RHS